A more-than-social movement: The post-human condition of quality in the early years. (March 2016) - Arndt, Sonja; Tesar, Marek
This article explores quality in early childhood education by de-elevating the importance of the human subject and experience, and heightening instead a focus on and tensions with the post-human. The argument traces the intricate web of 'qualities' woven throughout entanglements of subjects, objects and things that constitute what is referred to as 'the early years sector'. The strike through thesocial in this post-human condition exposes critical concerns about the 'problem' of quality, and foregrounds the urgency of rupturing the status quo. Dislodged from the perceived comfort and safety of human control and determination, quality in the speculative state of the more-than-social movement can expect no conclusion. Instead, the (re)configuration of the early years sector as a more-than-social movement compels a rethinking of the dominance of human-centric philosophies. By repositioning Kristeva's semiotic subject-in-process and Havel's subject positionings within automatisms, this analysis inserts 'non-human-being' and 'multiple beings-times' into the 'problem with quality'. In the early childhood sector, these ruptures create generative possibilities of quality entanglements with and beyond the human.